O uso de isótopos estáveis e radiogênicos na identificação e datação de águas subterrâneas, auxiliando a gestão de recursos hídricos - OLIVEIRA FILHO, Olavo Bilac Quaresma de (2019)
This work aims to show the rules, fundamentals and essential features of the use of stable and radiogenic isotopes in the identification and dating of groundwater, starting with studies of stable isotopes from hydrogen and oxygen and effects that reaches them, studies of water groundwater in local and regional level from alluded isotopes. This involves dating of groundwater using tritium, since questions about its formation (natural and anthropogenic), also stands out, its use to estimate flow velocities of water in the underground. The use of elemental carbon in a study of groundwater is treated at work, both its direct relationship in the composition of living and dating of groundwater (radiocarbon) with methods that seek greater precision in the calculation of the period of groundwater. At the end of the work, other topics are treated as the methodology for the study of these isotopes and case studies that show the potential of isotopic tool. Finally, the study seeks to relate the isotope geochemistry as a tool to assist water management setting important parameter for decision making by the relevant authorities.